PENGARUH CASH FLOW DAN LEVERAGE TERHADAP KINERJA PERUSAHAAN - Dias Anggi Pratiwi, (2017)
This study was conducted to examine the effect of variable Cash Flow and Leverage on Company Performance in Basic chemical industries in Indonesia Stock Exchange 2014-2016. The sampling in this study of 20 Basic chemical industries in Indonesia Stock Exchange 2014-2016 by purposive sampling method. Data obtained from the financial statements of the company which has been in publication. It is gained sample amount of 20 companies with 60 total sample. The analysis technique used here is multiple linear regression with a significance level of 5%. This research result indicates that (1) Cash Flow a significant effect on Company Performance (ROA), (2) Leverage (DER) a significant effect on Company Performance (ROA). Limitations of this study secondary data that has been obtained from the financial statements of the company shows that not all populations meet the criteria that have been set, thus reducing the number of samples used from 60 companies of basic chemical industry sectors in 2014-2016 listed on the Indonesia Stock Exchange to 20 companies.